PRECISION AGRICULTURE: the use of digital agriculture in the field - Cataneo, João Vitor; Cavichioli, Fabio Alexandre (Revista Interface Tecnológica, 2023)
An increasingly technological and globalized world has become one of the great motivators for the economic development of a nation, in order to increase productivity gains combined with sustainability. Thus, it is important that innovation is present in any corporate environment, being a key element for gains in competitiveness in a global market. In this sense, the agricultural sector has been using the new existing technologies as an efficient strategy to increase its gains in terms of productivity with sustainability. Therefore, the present study aimed to address the existing relationship between precision agriculture and digital agriculture in the field, with the intention of discussing the specificities and synergies between both. In order to obtain the data and information necessary for the theoretical contribution of this research, as well as to achieve the proposed objectives, bibliographic and documentary research were used as methods, in sources such as books, articles, monographs, magazines and other materials that have not yet been analyzed. scientific bias, such as reports and news. What was evidenced through this investigation is that there is a strong tendency to automate precision agriculture, mainly due to the increase in production costs, the reduction of labor, climate change, greater demands from food markets. in relation to safer food, always aiming at the conservation of natural resources through sustainable practices.